Peningkatan Keterampilan Penelitian Tindakan Sekolah untuk Pengembangan Profesi Guru: Improving School Action Research Skills for Teacher Professional Development - Nuriah, Yuyun; Dalmeri, Dalmeri; Supadi, Supadi (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The research was conducted by providing assistance to improve School Action Research (PTS) skills at the Permata Sari Foundation in Jakarta, which has approximately 30% of teachers with a pure science background, and 40% of young teachers have not received Teacher Professional Education (PPG). The condition of the teachers is a problem for the development of education at the foundation, so training is needed to conduct PTS. This assistance aims to provide knowledge and insight into 21st Century learning as a basis for teachers and Principals to plan PTS, so that they can improve the learning that is their responsibility. The assistance method is carried out by providing in-depth study of 21st Century learning materials, PTS theory, and providing guidance to teachers in planning PTS proposals. The assistance activities carried out by the Team from Indraprasta PGRI University were to increase insight and direct practice for teachers and Principals to prepare PTS Proposals. The assistance method was implemented by providing intensive training and practice in compiling PTS Proposals. The results of the study showed that teachers were able to plan PTS with the concept of 21st Century learning. There are five teachers who plan research in the realm of learning models, two teachers are interested in conducting PTS in the field of learning methods, two teachers plan PTS in improving learning media, and two teachers are interested in conducting action research in the field of attitudes and motivation. This study concludes that intensive and periodic mentoring with continued practice in a planned manner through online communication so that the PTS that have been made can be implemented by teachers and the Principal at the Permata Sari Foundation Jakarta, so that they can produce written works in the form of good articles.